Preparation and Properties of Oat Protein Amyloid Aggregate-Sodium Carboxymethyl Cellulose Composite Film - Liangliang WANG; Miaomiao HAN; Chongjiang CAO; Feng ZHOU (Shipin gongye ke-ji)
In order to improve the physicochemical properties of oat protein-based composite film, the natural oat protein (OP) was modified to prepare oat protein amyloid aggregates (OPA), and then the composite film was prepared with sodium carboxymethyl cellulose (CMCNa). The microstructure and properties of the composite films were studied by Fourier infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The mechanical properties, optical properties, moisture content, water solubility and water vapor permeability of the composite films were also determined. The results showed that the structure of the modified oat protein changed significantly. Compared with the OP/CMCNa composite film, the surface of the OPA/CMCNa composite film was smoother and the structure was more compact. Compared with OP/CMCNa composite film, the water solubility of OPA/CMCNa composite film was reduced by 7.02% to 15.84%, and the water resistance of OPA/CMCNa composite film was significantly improved. Among them, the puncture distance of the composite film prepared by OPA8 was increased to 6.513 mm, the force was increased to 701.2 g, and the mechanical properties were significantly improved. In conclusion, oat protein amyloid aggregates can effectively improve the transparency, water resistance and mechanical properties of natural oat protein-based composite films. The results can provide reference for the preparation and properties of modified oat protein composite film.